Temperature effects on clustering in TPX3-Si pixel detectors. (9th September 2021) - Leroy, C.; Papadatos, C.; Usman, M.; Boussa, M.
Abstract: The performance of a Timepix3 (TPX3) detector equipped with a 500 μm thick silicon sensor was evaluated while in vacuum and subjected to temperature variations. Proton beam measurements were performed at the Tandem Van de Graaff accelerator of the University of Montreal to determine the effect of sensor temperature on cluster parameters as well as measured energy. It was observed that temperature had a negative effect on the reconstructed energy obtained from the conventional calibration technique. The sizes of registered proton clusters increased as the sensor was heated up, indicating greater charge drift, resulting in additional charge sharing between neighbouring pixels.